COVID-19 Impact on Social and Economic Development of Regions of the Central Federal District of Russia - A. M. Asaliev; A. A. Stepanov; G. I. Avdeenko; S. G. Dmitriev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes the impact of COVID-19 pandemia and caused by it quarantine measures on social and economic development of certain regions of the Central Federal district of the Russian Federation, i. e. Bryansk, Voronezh, Ivanovo, Smolensk and Tula. Special attention is paid to small and medium business. The authors provide findings of the anonymous social survey carried out in the format of on-line questioning in the mentioned regions, which show public feelings in respect of restriction measures and steps of state support for business and relative expectations concerning prospects of regional entrepreneurial activity. The results of the survey showed that small and medium business suffered serious losses as a result of the pandemia. Economy restoration will be slow and long, according to respondents. Business of some respondents was ruined. The authors provide recommendations aimed at minimizing COVID-19 after-effects.